The first methadone programme in Malaysia: overcoming obstacles and achieving the impossible - Gill, J.S.; Sulaiman, A.H.; Habil, H. (2007)
Objectives: To determine the best possible programme that suits our local setting, to determine the average dose required, and to determine possible problems that can arise from implementing such a programme locally and how best to address them. Methods: The inclusion criteria were those above 18, a positive urine test, the presence of a supportive carer and willing to engage in the programme. Methadone was initiated and observations relating to dose, adverse events, relationship with carers, work performance, crime and high risk behaviours were monitored for 18 weeks. Results: Two thirds of the 45 subjects completed the trial over the 18 week period. No significant adverse events occurred and improvement in relationship with carers and work performance were noted with reduction in crime and high risk behaviours. Conclusion: Methadone is a safe and effective drug that can be used in the local Malaysian setting.